Sensing mechanisms of iron–sulfur cluster regulatory proteins elucidated using native mass spectrometry. Issue 23 (25th May 2021) - Crack, Jason C.; Gray, Elizabeth; Le Brun, Nick E.
Abstract : Native mass spectrometry provides novel insight into protein cofactor ( e.g. iron–sulfur cluster) chemistry. Abstract : The ability to sense and respond to various key environmental cues is important for the survival and adaptability of many bacteria, including pathogens. The particular sensitivity of iron–sulfur (Fe–S) clusters is exploited in nature, such that multiple sensor-regulator proteins, which coordinate the detection of analytes with a (in many cases) global transcriptional response, are Fe–S cluster proteins. The fragility and sensitivity of these Fe–S clusters make studying such proteins difficult, and gaining insight of what they sense, and how they sense it and transduce the signal to affect transcription, is a major challenge. While mass spectrometry is very widely used in biological research, it is normally employed under denaturing conditions where non-covalently attached cofactors are lost. However, mass spectrometry under conditions where the protein retains its native structure and, thus, cofactors, is now itself a flourishing field, and the application of such 'native' mass spectrometry to study metalloproteins is now relatively widespread. Here we describe recent advances in using native MS to study Fe–S cluster proteins. Through its ability to accurately measure mass changes that reflect chemistry occurring at the cluster, this approach has yielded a remarkable richness of information that is not accessible by other, more traditional techniques.